2001
DOI: 10.1111/j.1559-1816.2001.tb02742.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Toward Asian Americans: Theory and Measurement

Abstract: A theoretical framework to account for Whites' attitudes toward Asian Americans was developed and tested in 3 studies. An Attitude Toward Asians (ATA) scale was developed and found to be valid and reliable. Consistent with the framework, a negative factor and a positive factor were found to underlie attitudes toward Asian Americans. As expected, negative attitudes were shown to stem from both negative and positive instrumental attributes, whereas positive attitudes stemmed from positive instrumental and nonins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
191
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(197 citation statements)
references
References 40 publications
6
191
0
Order By: Relevance
“…Stereotypes tend to reflect perceptions held in society rather than real characteristics of groups (Sue and Kitano, 1973), and there have been limited studies on API youth and their families to counteract existing stereotypes. The false image can instigate negativity toward API, including resentment over their perceived success, and may contribute to an increase in hate crimes directed at API individuals (Ho and Jackson, 2001). In addition, even seemingly positive stereotypes can be mixed with underlying negative feelings toward the target group (Fiske et al, 2002).…”
Section: Two Sides Of the "Model Minority"mentioning
confidence: 99%
“…Stereotypes tend to reflect perceptions held in society rather than real characteristics of groups (Sue and Kitano, 1973), and there have been limited studies on API youth and their families to counteract existing stereotypes. The false image can instigate negativity toward API, including resentment over their perceived success, and may contribute to an increase in hate crimes directed at API individuals (Ho and Jackson, 2001). In addition, even seemingly positive stereotypes can be mixed with underlying negative feelings toward the target group (Fiske et al, 2002).…”
Section: Two Sides Of the "Model Minority"mentioning
confidence: 99%
“…They found that two sources were contributing to the negative attitudes and emotions expressed towards Asian Americans (Ho & Jackson, 2001). One was that Asian Americans were considered to be too good; that is, they were considered too intelligent or too competitive (Ho & Jackson, 2001).…”
mentioning
confidence: 99%
“…The hypothesis was that individuals feel Asian Americans constitute a realistic threat because they possess too many positive qualities (Ho & Jackson, 2001). The first study surveyed factors related to Asian Americans, including positive stereotypes, negative attitudes, and threats reported by participants, adapted from Stephan et al (2002).…”
mentioning
confidence: 99%
See 2 more Smart Citations